2022
DOI: 10.6023/cjoc202203060
|View full text |Cite
|
Sign up to set email alerts
|

Recent Process in the in situ Generated Metal Nanocluster Catalysis

Abstract: In transition metal catalyzed reactions using simple metal salts, metal complexes, or nanoparticles as catalyst precursors, the metal sources may transfer to other species in situ, such as mono metal species, metal clusters and nanoparticles. Herein, the representative examples of the in situ generated metal nanoclusters as the catalytically active species in synthetic methodologies are reviewed, including their in situ formation, characterization and effect in catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, this is the first observation that a nickel salt could be used for such a purpose. However, control experiments also showed that the addition of nickel nano-powder 23 has no effect on this step. The exact role of NiI 2 was not clear at the current stage.…”
Section: Resultsmentioning
confidence: 98%
“…To the best of our knowledge, this is the first observation that a nickel salt could be used for such a purpose. However, control experiments also showed that the addition of nickel nano-powder 23 has no effect on this step. The exact role of NiI 2 was not clear at the current stage.…”
Section: Resultsmentioning
confidence: 98%